WAYS TO IMPROVE IMPLEMENTATION OF INNOVATIONS IN THE FIELD OF AGRICULTURE IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2024)
The article presents ways to improve the introduction of innovations in agriculture. One of the main factors in the growth of production and employment in agriculture is the application and wide distribution of innovations. Practice shows that innovation is the most important source of improving product quality, saving labor and material costs, increasing labor productivity, improving production and increasing industry efficiency. As a result of the development of innovations, the competitiveness of manufactured products and enterprises in the domestic and foreign markets and the improvement of the socio-economic situation in the country's agrarian sector will be ensured. requires some changes in their relations.